Identification of Oligopeptides in the Distillates from Various Rounds of Soy Sauce-Flavored Baijiu and Their Effect on the Ester–Acid–Alcohol Profile in Baijiu - Qiang Wu; Shanlin Tian; Xu Zhang; Yunhao Zhao; Yougui Yu (Foods)
Endogenous peptides in Baijiu have primarily focused on finished liquor research, with limited attention given to the peptides in base liquor prior to blending. Liquid chromatography–tandem mass spectrometry (LC-MS) was employed to identify endogenous peptides in the distillates from the first to seventh rounds of soy sauce-flavored Baijiu. Two hundred and five oligopeptides were identified from these distillates, all of which had molecular weights below 1000 Da and were composed of amino acid residues associated with flavor (sweet, sour, and bitter) and biological activity. Furthermore, full-wavelength scanning, content determination of the main compounds, and molecular docking were performed to analyze these oligopeptides’ effect on the ester–acid–alcohol profile in Baijiu. This determination revealed a negative correlation between the peptide content and total ester content (r = −0.691), as well as the total acid content (r = −0.323), and a highly significant negative correlation with ethanol content (r = −0.916). Notably, the screened peptides (TRH, YHY, RQTQ, PLDLTSFVLHEAI, KHVS, LPQRHRMVYSLL, and NEWH) had specific interactions with the major flavor substances via hydrogen bonds, including esters (ethyl acetate, ethyl butanoate, ethyl hexanoate, and ethyl lactate), acids (acetate acid, butanoate acid, hexanoate acid, lactate acid), and alcohols (ethanol, 1-propanol, 1-butanol, and 1-hexanol). These findings elucidate the distribution and dynamic changes of endogenous peptides in the distillates from various rounds of soy sauce-flavored Baijiu, providing a theoretical foundation for further investigation into their interaction mechanisms associated with flavor compounds.